2015
DOI: 10.1371/journal.pone.0119017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Interventions That Include a Physical Activity Component in Class II and III Obese Individuals: A Systematic Review and Meta-Analysis

Abstract: BackgroundIn class II and III obese individuals, lifestyle intervention is the first step to achieve weight loss and treat obesity-related comorbidities before considering bariatric surgery. A systematic review, meta-analysis, and meta-regression were performed to assess the impact of lifestyle interventions incorporating a physical activity (PA) component on health outcomes of class II and III obese individuals.MethodsAn electronic search was conducted in 4 databases (Medline, Scopus, CINAHL and Sportdiscus).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 108 publications
9
70
0
3
Order By: Relevance
“…This was in line with a previous analysis by Galani et al [50]. Similarly, a meta-analysis by Baillot et al [51] demonstrated that long-term lifestyle interventions achieved a weight loss of 11.3 kg in those with Class II or III obesity. All three of these analyses further demonstrated that physical activity lifestyle changes were associated with improvements in metabolic risk profiles (waist circumference, fasting glucose, serum lipids, blood pressure) to varying degrees.…”
Section: The Role Of Physical Fitness: the Fit/fat Phenotypesupporting
confidence: 90%
“…This was in line with a previous analysis by Galani et al [50]. Similarly, a meta-analysis by Baillot et al [51] demonstrated that long-term lifestyle interventions achieved a weight loss of 11.3 kg in those with Class II or III obesity. All three of these analyses further demonstrated that physical activity lifestyle changes were associated with improvements in metabolic risk profiles (waist circumference, fasting glucose, serum lipids, blood pressure) to varying degrees.…”
Section: The Role Of Physical Fitness: the Fit/fat Phenotypesupporting
confidence: 90%
“…This intervention is especially beneficial for obese individuals (Baillot, et al 2015; Chin, et al 2016; Fock and Khoo 2013; Jakicic and Otto 2005), who commonly lead an overall sedentary lifestyle. In fact, physical activity is the most highly recommended intervention to prevent and slow weight gain, and lower BMI in obese children (Alkon, et al 2014; Bautista-Castaño, et al 2004; Lee, et al 2012).…”
Section: Feeding Behavior and Physical Activitymentioning
confidence: 99%
“…Whether exercise training is an important component of weightreducing strategy has been assumed for a long time [1] but strong evidence for this has been provided only quite recently [2]. High volumes of exercise are a powerful weight-reducing procedure, regardless the type of training (endurance or resistance) and its intensity [3].…”
Section: Introductionmentioning
confidence: 99%